ON A VERSION OF FIXED POINT THEOREM - Mikayelyan, L.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
In the present short note we prove a version of the classical fixed-point theorem, as well as present its application.
Keywords: Banach fixed-point